Problematizing Access to Higher Education for Refugee and Globally Displaced Students: What’s the Problem Represented to Be in Canadian University Responses to Syrian, Afghan and Ukrainian Crises? - Viczko, Melody; Matsumoto, Renata (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2022)
The UNHCR’s 15by30 campaign to increase refugee student enrolment in higher education to 15% by 2030 is a lofty goal. Canadian higher education institutions have a role to play in contributing to this policy goal, along with advocacy efforts from refugee student groups, community-based organizations, government, and international organizations. The aim of this study is to look critically at how the issue of access to higher education for refugee and globally displaced people is represented through Ontario’s universities’ responses to federal government initiatives to crises in Syria, Afghanistan and Ukraine. In this study, we use Bacchi’s (2009) “What’s the problem represented to be?” approach to policy analysis and, drawing on Dillabough’s (2022) critique of modernity in higher education, we argue that university responses related to refugee and globally displaced student access to higher education offer the possibility to reflect on the paradoxical tensions of the problem space in Canadian higher education. In our findings, we discuss how the problem of refugee and displacement crisis was represented differently in response to differences in geopolitical conditions and government policies, as we demonstrate how representations of material problems and categories of “citizenship” and “geographical location” in the universities’ responses contributed to creating boundaries of inclusion and exclusion for access. Finally, we show how the creation of educational programs for “globally displaced people” during the period related to the Ukrainian crisis perpetuates the logic of colonialism in the universities’ responses.